Between Foreigners and Shi`is: Nineteenth-Century Iran and Its Jewish Minority by Daniel Tsadik (Stanford, California: Stanford University Press, 2007. 295 pages.) (American Journal of Islam and Society, 2009)
After twenty-seven centuries of uninterrupted presence on the Persianplateau, the Jews of Iran have become so inextricably ingrained in everypossible aspect of Iranian life, culture, religion, and history that any valuablework of scholarship in Judeo-Persian studies, such as the one at hand,must by necessity entail an interdisciplinary approach. Between Foreignersand Shi`is, a ground-breaking work that will henceforth prove indispensableto any researcher ofmodern Judeo-Persian studies, is ameticulous pieceof scholarship that brings as much novelty to its own field as it does tomodernIranian historiography, Middle Eastern political studies, and Islamicstudies.Daniel Tsadik’s book provides a history of the religious, political, andsocial life of Iranian Jews under Naser al-Din Shah Qajar (r. 1848-96).Relying on a wealth of previously untapped archival material, the authorexamines in particular detail episodes of persecution in Barforush in 1866-67 (pp. 60-78), in Shiraz at the hands of Hajj Sayyid `Ali Akbar Fal Asiri(pp. 130-37), in Isfahan at the hands of ShaykhMohammad Taqi Najafi (pp.137-49), and in Hamadan at the hands of Mullah `Abdallah (pp. 155-77).Examining these and other episodes of anti-Semitic persecution against thebroader backdrop of socio-political events throughout Iran at large, such asthe Tobacco Rebellion of 1891 and the great famine, he brings to light a hithertounnoticed dynamic in which Iran’s Jewish community emerges as therope in a three-way tug of war between the Shi`ite clergy, the Qajar court,and western diplomats, with each jostling for dominance in the fledglingnation that was becoming modern Iran ...